MicroRNA-224 Suppresses Colorectal Cancer Cell Migration by Targeting Cdc42. (10th April 2014) - Ke, Tao-Wei; Hsu, Han-Lin; Wu, Yu-Hua; Chen, William Tzu-Liang; Cheng, Ya-Wen; Cheng, Chao-Wen
Abstract : The metastatic spread of tumor cells is the major risk factor affecting the clinical prognosis of colorectal cancer (CRC) patients. The metastatic phenotype can be modulated by dysregulating the synthesis of different structural and functional proteins of tumor cells. Micro(mi)RNAs are noncoding RNAs that recognize their cognate messenger (m)RNA targets by sequence-specific interactions with the 3′ untranslated region and are involved in the multistep process of CRC development. The objective of this study was to investigate the expression and biological roles of miR-224 in CRC. The miR-224 expression level was assessed by a quantitative real-time PCR in 79 CRC and 18 nontumor tissues. Expression levels of miR-224 in CRC tissues were significantly lower than those in nontumor tissues. Its expression level was associated with the mutation status of the APC gene. Ectopic expression of miR-224 suppressed the migratory ability of CRC cell line, but cell proliferation was less affected. Increased miR-224 diminished Cdc42 and SMAD4 expressions at both the protein and mRNA levels and inhibited the formation of actin filaments. Overall, this study indicated a role of miR-224 in negatively regulating CRC cell migration. The expression level of miR-224 may be a useful predictive biomarker for CRC progression.